(untitled) (Okhaldhunga Journal, 2024)
This article entitled Critical Friends Group (CFG) for English Language Teachers’ Professional Development aims to investigate teachers’ perceptions towards CFG for English Language Teachers’ Professional Development. The data was collected from five English language teachers teaching in a government school by using semi-structured interview. This is a qualitative research method based on narrative inquiry. The participants were selected by using judgemental non- random sampling procedures. The findings showed that teachers perceived CFG as one of the plausible means of their professional development. It helps to foster collaborative and critical learning in them because they are involved in observation, reading and discussion of various burning issues of English language teaching and learning. It also indicated that teachers perceived CFG as the best platform for enhancing the personal, social and professional development. It has enhanced the professionalism on the part of teachers cultivating the sense of mutual trust and understanding between and among the colleagues.